The strategic adaptation of Chinese-Manadonese in the Reform Era - Waworuntu, Adrianus L.G.; Alkatiri, Zeffry; Gani, Fuad (UI Scholars Hub, 2017)
This article is a further discussion of previous research which is a pilot project to observe patterns of cultural interaction within the Chinese community in Indonesia as a part of a project to understand the phenomenon of the multicultural society during the New Order Era. The specific target of this research is to study the socio-cultural interactions within the Chinese community in Manado during the Reform Era (2000-2014). This research aims to study the strategic adaptation of the Chinese in Manado, by analysing the obstacles and opportunities in their socio-cultural interaction with the locals. Using data from field research and literature studies, this qualitative research applies an ethnographic approach by observing various actions in their socio-cultural interactions.